(untitled) (Global Journal of Medical Research, 2019)
Concomitant fracture of lateral humeral condylar physis along with dislocation of the elbow is a rare entity. There is a paucity of literature on the topic with previous citation being isolated case reports or case series of 3-4 cases. Inasmuch as the treatment of lateral condyle is open reduction internal fixation, it is imperative that standard protocols are followed in order to expect a good outcome. We report a case of 11 year old male child with such an injury who was managed with operative intervention followed by excellent outcome. Subsequently we wish further add upon the existing limited knowledge on the management of this complex injury pattern.